Ca2+ ionophores are not suitable for inducing mPTP opening in murine isolated adult cardiac myocytes - Mathieu Panel (Nature Portfolio, 2017)
Abstract Opening of the mitochondrial permeability transition pore (mPTP) plays a major role in cell death during cardiac ischaemia-reperfusion. Adult isolated rodent cardiomyocytes are valuable cells to study the effect of drugs targeting mPTP. This study investigated whether the use of Ca2+ ionophores (A23187, ionomycin and ETH129) represent a reliable model to study inhibition of mPTP opening in cardiomyocytes. We monitored mPTP opening using the calcein/cobalt fluorescence technique in adult rat and wild type or cyclophilin D (CypD) knock-out mice cardiomyocytes. Cells were either treated with Ca2+ ionophores or subjected to hypoxia followed by reoxygenation. The ionophores induced mPTP-dependent swelling in isolated mitochondria. A23187, but not ionomycin, induced a decrease in calcein fluorescence. This loss could not be inhibited by CypD deletion and was explained by a direct interaction between A23187 and cobalt. ETH129 caused calcein loss, mitochondrial depolarization and cell death but CypD deletion did not alleviate these effects. In the hypoxia-reoxygenation model, CypD deletion delayed both mPTP opening and cell death occurring at the time of reoxygenation. Thus, Ca2+ ionophores are not suitable to induce CypD-dependent mPTP opening in adult murine cardiomyocytes. Hypoxia-reoxygenation conditions appear therefore as the most reliable model to investigate mPTP opening in these cells.